Cytokines in Cancer Immunotherapy - Waldmann, Thomas A (Cold Spring Harbor perspectives in biology, 2018)
Cytokines that control the immune response were shown to have efficacy in preclinical murine cancer models. Interferon (IFN)-α is approved for treatment of hairy cell leukemia, and interleukin (IL)-2 for the treatment of advanced melanoma and metastatic renal cancer. In addition, IL-12, IL-15, IL-21, and granulocyte macrophage colony-stimulating factor (GM-CSF) have been evaluated in clinical trials. However, the cytokines as monotherapy have not fulfilled their early promise because cytokines administered parenterally do not achieve sufficient concentrations in the tumor, are often associated with severe toxicities, and induce humoral or cellular checkpoints. To circumvent these impediments, cytokines are being investigated clinically in combination therapy with checkpoint inhibitors, anticancer monoclonal antibodies to increase the antibody-dependent cellular cytotoxicity (ADCC) of these antibodies, antibody cytokine fusion proteins, and anti-CD40 to facilitate tumor-specific immune responses.